0.167
Chat with our AI personalities
It's an algebraic expression that can be simplified to: x-5y
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
bringing across the =, 5x = -10 so x = -2
-6x+9 = 45 -6x = 45-9 -6x = 36 x = -6
To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.